The Physical Condition of Household Environment and History of Acute Respiratory Infection (ARI) to the Stunting Cases in Ogan Ilir Regency - Nita Amelia Putri; Rahmatillah Razak; Yusri; Inoy Trisnaini; Arizky Ramadhan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: The case of stunting in toddlers can be caused by infectious diseases such as acute respiratory infection as the direct factor and the physical conditions of the household environment as the indirect factor. This study aims to determine the relationship between the physical condition of the household environment and history of Acute Respiratory Infection (ARI) to the stunting cases in toddlers in 13 stunting locus villages in Ogan Ilir Regency 2024. Method: This study used a case-control study focusing on stunted toddlers aged 24-59 months in 13 locus villages in Ogan Ilir Regency. A total of 129 samples of under-fives were obtained using the Lameshow formula, with a ratio of 1:2 found (43 cases and 86 controls). Inclusion criteria were stunted toddlers for cases and non-stunted toddlers in the neighborhood for controls. This study examined various factors including wall type, floor type, ceiling type, residential density, temperature, humidity, lighting, ventilation, and history of acute respiratory infections (ARI). Data analysis included univariate, bivariate (using chi-square test), and multivariate (using multiple logistic regression) methods. Result: The bivariate analysis showed a significant association between residential density (p-value = 0,010), ventilation (p-value = 0,002), history of acute respiratory infection (ARI) (p-value = 0,000), moderate ARI severity (p-value = 0,000), and one-time ARI frequency (p-value = 0,001) with the stunting cases in Ogan Ilir Regency. Multivariate analysis identified history of ARI as the dominant factor influencing stunting in toddlers (OR = 13,458 95% CI 3,618 – 50,063). Conclusion: This study conducted in 13 villages of Ogan Ilir regency found that factors such as residential density, ventilation, and a history of acute respiratory infections (ARI) were significantly linked to stunting in children aged 24 to 59 months with the history of ARI was the dominant factor against stunting in toddlers.